Effect of a Targeted Women's Health Intervention in an Inner-City Emergency Department. (10th December 2011) - Houry, Debra; Hankin, Abigail; Daugherty, Jill; Smith, L. Shakiyla; Kaslow, Nadine
Abstract : Objective. To evaluate the effect of an Emergency Department (ED) based, educational intervention for at-risk health behaviors. Methods. A randomized trial over a one-year period. African American women, aged 21–55, presenting to the ED waiting room were eligible. Each participant took a computer-based survey on health risk behaviors. Participants who screened positive on any of four validated scales (for IPV, nicotine, alcohol, or drug dependence) were randomized to standard information about community resources (control) or to targeted educational handouts based upon their screening results (intervention). Participants were surveyed at 3 months regarding contacts with community resources and harm-reduction actions. Results. 610 women were initially surveyed; 326 screened positive (13.7% for IPV, 40.1% for nicotine addiction, 26.6% for alcohol abuse, and 14.4% for drug abuse). 157 women were randomized to intervention and 169 to control. Among women who completed follow-up (n = 71 ), women in the Intervention Group were significantly more likely to have contacted local resources (37% versus 9%, P = 0.04 ) and were more likely to have taken risk-reducing action (97% versus 79%, P = 0.04 ). Conclusion. Targeted, brief educational interventions may be an effective method for targeting risk behaviors among vulnerable ED populations.